Safety aspect in management of construction project / Janidah Eman...[et al.] - Eman, Janidah; Hassan, Siti Hafizan; Ahzahar, Nadira; Ahmad, Hazrina (2010)
One of the safety aspects that always emphasized by the government is using the safety equipments at construction sites. It is because most of the accident cases that have been reported currently in construction industry are usually related to this matter. As the consequence from the increasing of the accident cases, employers have to ensure that the standards and enrolments lay down by the law (especially statutes) in order to ensure the compliance is more effective. The employee themselves must also comply with the standard and requirements for their own safety while working at site. To make Malaysia become more aware of safety, it is hope that safe work procedure can be improve. The parties that involved are responsible in complying standard of work safety especially in provided and using of safety equipment. This matters are not only to the employer (the contractor), but also to the parties as well, such as consultants, clients and the employees. Some of the basic statutory requirement in using safety equipment relating to safety at workplaces (i.e. the construction site) is specified in Occupational Safety and Health Act 1994 and Factories and Machinery Act 1967.This research solely discusses matters relating to this requirement and compliance of using safety equipment by workers while working at site. Questionnaires are also posted to several different parties that involved in the said matters. The result shows that almost all parties especially employer and workers, are aware of the requirements but still at a lower level of its compliance.